2013
DOI: 10.1089/ten.tea.2012.0330
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Elastomeric Scaffolds Designed with Cardiac-Mimetic Structural and Mechanical Features

Abstract: Tissue-engineered constructs, at the interface of material science, biology, engineering, and medicine, have the capacity to improve outcomes for cardiac patients by providing living cells and degradable biomaterials that can regenerate the native myocardium. With an ultimate goal of both delivering cells and providing mechanical support to the healing heart, we designed three-dimensional (3D) elastomeric scaffolds with (1) stiffnesses and anisotropy mimicking explanted myocardial specimens as predicted by fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 75 publications
1
88
0
1
Order By: Relevance
“…In some tissue engineering applications, such as nerve and skin regeneration, the linear, low-strain region of the stress-strain curve was used to calculate the elastic modulus of samples and considered to represent physiological behavior in the human vasculature (Amensag and McFetridge, 2014). In a similar study, isotropic linear elastic behavior was reported and 10% strain used to calculate the elastic modulus of scaffolds fabricated as cardiac-mimetic structures; furthermore, 10 to 25% strain was reported as the cardiac-relevant strain range in physiological conditions (Neal et al, 2012). Finally, a finite element study assigned linear elastic elements to a model to predict the mechanical properties of tissue-engineered cartilage constructs (Sengers et al, 2004).…”
Section: Effect Of Crosslinker Volumementioning
confidence: 99%
“…In some tissue engineering applications, such as nerve and skin regeneration, the linear, low-strain region of the stress-strain curve was used to calculate the elastic modulus of samples and considered to represent physiological behavior in the human vasculature (Amensag and McFetridge, 2014). In a similar study, isotropic linear elastic behavior was reported and 10% strain used to calculate the elastic modulus of scaffolds fabricated as cardiac-mimetic structures; furthermore, 10 to 25% strain was reported as the cardiac-relevant strain range in physiological conditions (Neal et al, 2012). Finally, a finite element study assigned linear elastic elements to a model to predict the mechanical properties of tissue-engineered cartilage constructs (Sengers et al, 2004).…”
Section: Effect Of Crosslinker Volumementioning
confidence: 99%
“…Other aspects being investigated include the modulation of material architecture (37) and the incorporation of conductive materials, such as nanotubes (18), to improve myocyte morphology and function. In addition, investigators are trying to determine which cell types should be delivered to the injured area to achieve the greatest improvement in cardiac function (i.e.…”
Section: Repair Using Cardiac Patchesmentioning
confidence: 99%
“…In this approach, cells are seeded onto the scaffolds before going through tissue maturation. In scaffold fabrication, several methods, such as solvent casting [28][29][30] , molding [31] and electrospinning [32][33][34][35][36][37][38] , have been used. Features on the fabricated scaffolds can affect cell responses directly.…”
Section: Conventional Techniques In Cardiac Tissue Engineeringmentioning
confidence: 99%